Resistance to cellular autophagy by Mycobacterium tuberculosis Beijing strains. Issue 7 (October 2015) - Haque, Md Fazlul; Boonhok, Rachasak; Prammananan, Therdsak; Chaiprasert, Angkana; Utaisincharoen, Pongsak; Sattabongkot, Jetsumon; Palittapongarnpim, Prasit; Ponpuak, Marisa
Autophagy represents a key pathway in innate immune defense to restrict Mycobacterium tuberculosis growth inside host macrophages. Induction of autophagy has been shown to promote mycobacterial phagosome acidification and acquisition of lysosomal hydrolases, resulting in the elimination of intracellular M. tuberculosis reference strains such as H37Rv. The notorious Beijing genotype has been previously shown to be hyper-virulent and associated with increased survival in host cells and a high mortality rate in animal models, but the underlying mechanism that renders this family to have such advantages remains unclear. We hypothesize that autophagic control against M. tuberculosis Beijing strains may be altered. Here, we discovered that the Beijing strains can resist autophagic killing by host cells compared with that of the reference strain H37Rv and a strain belonging to the East African Indian genotype. Moreover, we have determined a possible underlying mechanism and found that the greater ability to evade autophagic elimination possessed by the Beijing strains stems from their higher capacity to inhibit autophagolysosome biogenesis upon autophagy induction. In summary, a previously unrecognized ability of the M. tuberculosis Beijing strains to evade host autophagy was identified, which may have important implications for tuberculosis treatment, especially in regions prevalent by the Beijing genotype.